EFFECT OF CIRCUIT TRAINING METHOD ON VERTICAL JUMP WOMEN IN VOLLEYBALL EXTRACURRICULAR ACTIVITIES AT MANIAMAS NGABANG HIGH SCHOOL - Wanda Firdaus; Eka Supriatna; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2022)
AbstractThe problem in this study is the ability of vertical jumps in volleyball players at Maniamas Ngabang High School, who follow volleyball extracurricular activities are still categorized as less and the circuit training method has not been implemented yet. The purpose of this research is